FLOOD MITIGATION WITH POLDER SYSTEM IN MELATI CIDENG CENTRAL JAKARTA - AMRULLAH - Nim: 15813008 , SONY
Flooding in Jakarta has been a recurring problem every year. In this final project about the polder system for flood control especially in Melati Cideng Central Jakarta with an area of 791 ha. The problems that occur in the location of the study need to get attention because Central Jakarta is a barometer of the achievement of development results in this country because it has enormous potential such as economic resources, infrastructure and so forth. In identifying the problem, an analysis of rainfall data, river and pump sections can be done to flood mitigation in the area. For polder system planning include hydrological analysis, flood modeling and building design planning. The design rainfall is calculated by Normal, Normal Log, Pearson Log Type III, Gumbel method. Flood discharge is calculated by the method of SCS and Nakayashu return period 25th. Flood modeling using HEC-RAS and SWMM. From the results of planning analysis, obtained drainage system consisting of channels, trash rack, pond storage and pump house.